Foundations of geological carbon storage modelling and the Atlantic Canada context - Skinner, Carla (Atlantic Geoscience, 2025)
Geological Carbon Storage (GCS) is an essential climate mitigation strategy, enabling the long-term storage of carbon dioxide (CO₂) in deep subsurface formations. Offshore Atlantic Canada offers significant potential due to favourable geology, extensive subsurface data, and infrastructure from past hydrocarbon development. Major sedimentary basins such as the Scotian, Jeanne d’Arc, and Orphan contain structural traps, thick saline aquifers, and effective caprock seals that are critical for secure CO2 storage. Successful GCS depends on robust geological modelling workflows that incorporate subsurface heterogeneity, trapping mechanisms, and containment integrity. This paper reviews the foundational components of geological models - structural, stratigraphic, geometric, and topological frameworks – combined with numerical simulators to predict plume migration, pressure evolution, and geochemical interactions. Modelling supports all project stages, from site screening to post-injection monitoring, and is guided by parameters such as capacity, injectivity, containment, and storage efficiency. International offshore analogs such as Sleipner, Snøhvit, Northern Lights, Tomakomai, and Porthos provide valuable lessons in infrastructure reuse, regulatory development, and public engagement. These projects highlight the importance of tailored monitoring and verification plans, hub-based infrastructure models, and early-stage demonstration projects to build public trust. Offshore Atlantic Canada faces unique challenges including complex structural geology, overpressure zones, and salt tectonics, necessitating detailed technical evaluation. Recommended actions include high-resolution geologic modelling, probabilistic capacity assessments, and the creation of a regional carbon storage atlas. As regulatory frameworks evolve and carbon management becomes increasingly urgent, offshore Atlantic Canada is well-positioned to become a leader in safe, large-scale geological CO₂ storage.